The synmetamorphic P-T-f path of granulite-facies gneisses from Torngat Orogen, and its bearing on their tectonic history - Mengel, Flemming; Rivers, Toby (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1990)
Summary Granulite-facies gneisses in the Ablovlak shear zone in the internides of the Torngat Orogen are characterized by subvertical shear fabrics and associated subhorizontal stretching lineations. P-T vectors, derived from individual samples of these gneisses by conventional geothermobarometry of equilibrium core, rim and replacement symplectite assemblages, yield evidence of over 3k bars decompression associated with cooling of approximately 150°C. When the sample population is considered together, a P-T-fpath involving over 5 kbars decompression and 250°C cooling is defined. Such paths are compatible with theoretical models of synmetamorphic uplift following doubling of crustal thickness during thrusting, and imply that transcurrent motion took place in tectonically thickened crust, and was coeval with uplift. In a regional context, the Torngat Orogen preserves evidence of the oblique collision of two Archean cratonic blocks, the Nainand Rae provinces, during the Early Proterozoic and their a malgamation with Laurentia.